Recent books on digital research methodology for social scientists: An overview - Sokolovskiy, Sergei V. (Сибирские исторические исследования)
The article presents a brief consideration of recent methodological publications on digital methods in social sciences and humanities, written by the leading specialists in the field of contemporary digital media research. The methods discussed are often subdivided into two main groups, the first one referring to uniquely digital methodologies applied by social scientists for understanding digital technologies and their roles in such disciplines as science and technology studies, techno-anthropology, anthropology and sociology of media, etc.; the second one, pertaining to traditional methods of social and cultural research, is applied to new cyber-media and thus adapting and transforming these methods to what is perceived (compared to classical fieldwork sites and locations) as a radically new environment. The review is focused on the current needs of digital anthropological research, although it is not limited to socio-cultural anthropology and ethnology. As each of the publications and/or methods discussed is adjusted to a certain range of objects or subjects of study that could be thematically classified, their inclusion in this review pays attention to such thematic fields as cyberidentity, users' interests and behavior, digital mediation, ethics of online research, and societal and technological innovation and change.